MA'RIFATULLA>H>H DAN KEARIFAN LINGKUNGAN DALAM PUISI - Arif Hidayat (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2012)
This article reveals the relation among, God, man, and nature inZainal Arifin Thoha poems. There are many Muslims thinkers who manifesttheir way of life in poems to project themselves, God and the universe.This is because poem could take in all the beauty and feeling thatcome in live. To understand those poems, it is needed takwil (interpretation)rules. The hermeneutic interpretation is used to find out the realshape of the reality (haqa>’ iq al-wuju>d) which is manifested in poems.This article shows that there is a spiritual transformation which is broughtinto reality from the poems by oneself. This is the transformation from aprayer which is moved actively from the poetic nuance from the depth ofsoul.